Effect of Captopril on Toll Like Receptor Expression in Adjuvant Induced Arthritis - Assim Oday Farooq; Nadia Hameed Mohammed (College of Pharmacy / Mustansiriyah University, 2022)
Rheumatoid arthritis (RA) is an inflammatory disease with autoimmune origin that affect joints firstly and then progress to be a systemic disease. Toll like receptor (TLR) play an important role in the evolution and progression of this disease. Captopril is an angiotensin enzyme inhibitor (ACEI) that is widely used to control elevation in the blood pressure. This drug has anti-inflammatory activities, for this reason we try to investigate its action in RA. In this study we found that captopril decreases both expression and intensity of TLR2.